2017
DOI: 10.5539/gjhs.v9n8p32
|View full text |Cite
|
Sign up to set email alerts
|

What If All Patients with Breast Cancer in Malaysia Have Access to the Best Available Care: How Many Deaths Are Avoidable?

Abstract: Background: Cancer is a leading cause of death in the world and the fourth leading cause in Malaysia. A widening disparity in cancer burden has emerged between high and low-middle income countries. A similar disparity due to differential access to cancer care between affluent and deprived groups is likely to exist within developing country too. We assess this inequality by estimating the number of deaths due to cancer that would be avoidable if all patients had access to the best available care in Malaysia, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
1
7
0
3
Order By: Relevance
“…In addition, the mortality rate is higher among patients receiving treatment in public hospitals than in private hospitals. This is in line with the study conducted by Ho, et al (2017) found that almost 2048 (88%) cases of death due to breast cancer in Malaysia could be avoided because 1167 (57%) cases were due to late patients in screening. While 881 (43%) cases of death due to not receiving complete treatment which indirectly indicates that there is a difference between the socioeconomic status of patients.…”
Section: Introductionsupporting
confidence: 90%
“…In addition, the mortality rate is higher among patients receiving treatment in public hospitals than in private hospitals. This is in line with the study conducted by Ho, et al (2017) found that almost 2048 (88%) cases of death due to breast cancer in Malaysia could be avoided because 1167 (57%) cases were due to late patients in screening. While 881 (43%) cases of death due to not receiving complete treatment which indirectly indicates that there is a difference between the socioeconomic status of patients.…”
Section: Introductionsupporting
confidence: 90%
“…28 Na Malásia, observouse que cerca de 50% a 88% das mortes seriam evitáveis se o diagnóstico do câncer fosse precoce e os indivíduos tivessem um acesso ideal ao serviço. 29 Reforça-se, portanto, a importância de que os pacientes diagnosticados com neoplasias devem ter acesso imediato ao tratamento ideal, para otimizar as chances de sobrevida.…”
Section: Discussionunclassified
“…Estudo aponta que grande número de mortes evitáveis se deve em grande parte ao acesso diferenciado ao tratamento do câncer entre os grupos com maior poder aquisitivo e carentes, e que muitas das mortes seriam evitáveis, principalmente se serviços de boa qualidade fossem acessíveis a toda a população feminina 15 .…”
Section: Discussionunclassified